2020
DOI: 10.3390/rs12244101
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Model for Prediction of Short-Term Heavy Precipitation Based on GNSS-Derived PWV

Abstract: Nowadays, the Global Navigation Satellite Systems (GNSS) have become an effective atmospheric observing technique to remotely sense precipitable water vapor (PWV) mainly due to their high spatiotemporal resolutions. In this study, from an investigation for the relationship between GNSS-derived PWV (GNSS-PWV) and heavy precipitation, it was found that from several hours before heavy precipitation, PWV was probably to start with a noticeable increase followed by a steep drop. Based on this finding, a new model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…In any column of air, the amount of water vapor, or precipitable water vapor (PWV), provides an upper limit to the potential precipitation which could fall from that column of air [1]. In particular, many studies have confirmed that PWV variations can effectively reveal the occurrences and the life cycles of precipitation events [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In any column of air, the amount of water vapor, or precipitable water vapor (PWV), provides an upper limit to the potential precipitation which could fall from that column of air [1]. In particular, many studies have confirmed that PWV variations can effectively reveal the occurrences and the life cycles of precipitation events [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…where T s is the surface temperature ( • C) of the site. More information regarding the retrieval of GNSS-PWV can be found in our previous study [17], in which the accuracy of the retrieved GNSS-PWV at the HKSC station was also evaluated, with a root mean square error of 2.2 mm, and proved to be acceptable for meteorological research.…”
Section: Gnss-pwvmentioning
confidence: 99%
“…However, these monthly thresholds were often given empirically or selected from a certain value range [15,27]. In our recent study [17], an optimal set of monthly precipitation thresholds were determined based on the CSI, and the threshold for each predictor was unique for each of the three summer months. Generally, the method for the determination of monthly precipitation thresholds for a predictor based on the CSI mainly contained the following steps: (1) A set of candidate threshold values are selected, and the principles for the selection is elaborated in Section 3.3.1; (2) the above candidate threshold values, together with the GNSS-PWV sample data and precipitation records, were used to calculate n 11 , n 12 , and n 21 in Equation ( 5) during the period for thresholds determination, e.g., the 8 years from 2010 to 2017 our previous study [17]; (3) the CSI score resulting from each of the candidate thresholds was calculated using Equation ( 5), and the candidate threshold value that leads to the highest CSI score was determined as the optimal threshold.…”
Section: Determining Monthly Precipitation Thresholds Based On Csimentioning
confidence: 99%
See 2 more Smart Citations